Two-stage copper(II) and nickel(II) removal using rubber wood shavings and strontium alginate immobilized bacteria - Nordin, Nordiana (2009)
The increasing level of heavy metals in aquatic system due to incomplete treatment of industrial wastewater by existing conventional methods is of environmental concern. Therefore, there has been an increasing interest on the possibility of using biological treatments such as biosorption in the abatement of heavy metal–contaminated wastewater. In this study, a two-stage process for Cu(II) and Ni(II) removal has been developed. The first stage involves biosorption of Cu(II) and Ni(II) ions by rubber wood shavings (RWS) followed by a polishing stage where the remaining metal ions exist in the wastewater will be adsorbed by dead bacterial biomass immobilized in alginate matrix (Strontium Alginate Immobilized Bacteria, SAIB) prior to discharge. Acinetobacter haemolyticus, Acinetobacter calcoaceticus, Clavibacter agropyri and Cellulosimicrobium cellulans were tested for growth in cheap carbon sources i.e. liquid pineapple waste (LPW) and brown sugar and tolerance towards Cu(II) and Ni(II). SAIB and NaOH–treated RWS were subjected to Cu(II) and Ni(II) removal studies where parameters such as contact time, adsorbent dosage and initial metal concentrations were optimized. Both LPW and brown sugar can serve as an alternative and cost-effective growth medium for largescale cultivation of bacteria. Supplementation of brown sugar with tryptone gave the highest biomass yield. Bacterial growth in LPW were greatly affected after addition of metal especially Cu(II) indicating the toxic effect. A. haemolyticus was chosen for biosorption study as it is the most tolerant strain where it can resist up to 25 mg L-1 of Cu(II) and 500 mg L-1 of Ni(II). From the biosorption study using RWS and SAIB, contact time of 5 hours and initial metal concentration of 100 mg L-1 were optimized. Nevertheless, the adsorbent dosage for RWS and dried SAIB bead varies with values of 3% (w/v) and 0.025g respectively. The Cu(II) and Ni(II) adsorption using RWS and SAIB in single and mixed metal solution occurs as monolayer coverage as confirmed by Langmuir and Freundlich isothermal analysis. However, the Ni(II) adsorption by RWS in mixed metal solution cannot be modeled by both isotherms. FTIR and FESEM–EDAX analysis suggest the removal of Cu(II) and Ni(II) by A. haemolyticus was due to electrostatic interaction or complexation of the metal ions with the functional groups such as hydroxyl, carbonyl, amide and sulphamide present on the cell wall. The integration of biosorption processes using RWS and SAIB resulted in 77.8 % Cu(II) and 64.1 % Ni(II) removal from the electronic wastewater.